Development of FPGA based smart traffic light controller system with image processing - Tan, Keng Shuen (2019)
As the population of the city, as well as the number of automobiles travel on the roads are increasing day by day, traffic congestion at the junctions is becoming a huge problem for many major cities nowadays. One of the reasons behind this traffic issue is the inefficiency of the techniques and algorithms used in the existing traffic light system which unable to adapt to the continuous changing traffic situation and eventually lead to traffic congestion spreads and occurrence of road accidents increase. Therefore, to prevent the situations further deteriorate, there is a pressing need for the introduction of advanced system and technology that able to improve the current traffic light control system to better accommodate this increasing demand.